Multilevel analysis of factors influencing innovation through m-TISM approach. (8th July 2022) - Hasan, Zuby; Parameswar, Nakul; Ongsakul, Viput
This paper explores the factors affecting innovation at three distinct levels – firm, industry and country level and analyses the relationship amongst the factors in each level. The list of factors has been identified through literature search and further using inputs from academicians, practitioners and policymakers' contextual relationship amongst the factors that have been studied. Modified total interpretive structural modelling (m-TISM) has been utilised to examine the driving and dependence power of factors at each level and develop a hierarchical model. Overall, this paper analyses 14 factors affecting innovation across firm, industry and country level. Results show that antecedents such as knowledge acquisition, research and development at the organisational level have high driving power and significant impact on innovation as knowledge itself serves as the basis of innovation, and business sophistication is an important factor for enhancing innovation capacity and economic growth at a country level. Furthermore, organisational encouragement and quality of human resources are important factors that promote creativity and innovation at the industry level. Entrepreneurs, academicians and government can focus on the factors identified and define strategies for enhancing innovation in the organisations or in the country.